2015
DOI: 10.1213/xaa.0000000000000188
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Continuous Quadratus Lumborum Block for Acute Postoperative Abdominal Pain as a Rescue After Opioid-Induced Respiratory Depression

Abstract: We present a case of acute postoperative abdominal pain after proctosigmoidectomy and colorectal anastomosis that was treated by bilateral continuous quadratus lumborum block. The block was performed in the lateral position under ultrasound guidance with a 15-mL bolus of 0.5% bupivacaine injected anterior to the quadratus lumborum muscle followed by bilateral catheter placement. Each catheter received a continuous infusion of 0.1% bupivacaine at 8 mL/h and an on-demand bolus 5 mL every 30 minutes. Sensory leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 17 publications
1
23
0
Order By: Relevance
“…The effective pain relief lasted for 12-14hours. Prolonged and continuous pain relief has been reported with catheter techniques for acute abdominal pain management [15] breast reconstruction [16] and laparotomy [11]. However, they all have used type-2 quadratus lumborum block.…”
Section: Discussionmentioning
confidence: 99%
“…The effective pain relief lasted for 12-14hours. Prolonged and continuous pain relief has been reported with catheter techniques for acute abdominal pain management [15] breast reconstruction [16] and laparotomy [11]. However, they all have used type-2 quadratus lumborum block.…”
Section: Discussionmentioning
confidence: 99%
“…This extensive cutaneous sensory block is consistent with case reports published to date. 39,200,203,206 Promising results with continuous catheter techniques have also been reported for both children and adults. 39,200,204,206 These early data are encouraging for the efficacy of the QL block, and further investigation is warranted.…”
Section: Us-guided Quadratus Lumborum Blockmentioning
confidence: 99%
“…The early descriptions exist primarily as conference abstracts and e-letters, and most of our knowledge comes from case reports. 39,200,[203][204][205][206] Blanco et al 207 recently published the first RCT of the QL2 block and demonstrated that when added to a multimodal analgesic regimen of acetaminophen and NSAIDs (but no intrathecal morphine) in patients undergoing elective cesarean delivery it reduced opioid requirements and pain scores in the first 24 to 48 hours. In another study, Murouchi et al 49 compared a prospective cohort of 11 patients undergoing laparoscopic gynecologic surgery who received bilateral QL2 blocks to a historical cohort of patients who received bilateral TAP blocks.…”
Section: Us-guided Quadratus Lumborum Blockmentioning
confidence: 99%
“…This new block had a wider coverage of dermatomes,11 included visceral blockade and lasted longer than TAP block, and became known as the QL block. More recently, it has been reported that bilateral continuous QL blocks can provide extended postoperative analgesia,12 even after major abdominal surgery 13…”
Section: Discussionmentioning
confidence: 99%